Analisis Polarisasi Dualisme dan Pluralisme Hukum Islam di Indonesia - Muhammad Yusril; Mhd Dayrobi; Hilal Haitami Harahap; Zainul Fuad (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Some people still think that everything contained in the books of fiqh is sacred and no one is competent to change it. In fact, the tendency that occurs is that it is very difficult for them to accept the changes that occur in society today. Various ideas for reforming Islamic law have also colored the dynamics of Islamic legal thought in Indonesia, which is essentially the response of Islamic legal thinkers to modernization and development. Thus, this journal will discuss Polarization, Dualism and the Dynamics of Islamic law in Indonesia. This research uses qualitative research with a literature data or literature study approach. The data collection method is by using literature (libraries) from the books Treatise on Marriage Law, National Marriage Law, and the Struggle for Islamic and Customary Law in Indonesia. The research results show that there are two currents of thought which then give rise to dualism and pluralism of sirri marriage law in Indonesia. First group. states that a marriage/marriage is actually valid if it fulfills the pillars and conditions as stipulated by religious teachings. However, the second group states that even though a marriage/marriage has been carried out in compliance with the pillars and requirements according to religious provisions, it is still considered invalid before the law as long as it has not been registered and authentic evidence of the marriage event has not been obtained.